Evaluation of Gait and Functional Stability in Preoperative Cervical Spondylotic Myelopathy Patients. Issue 4 (15th February 2022) - Hassanzadeh, Hamid; Bell, Joshua; Dooley, Evan; Puvanesarajah, Varun; Kamalapathy, Pramod; Labaran, Lawal; Shimer, Adam; Shen, Francis; Russell, Shawn
Abstract : Prospective data of biomechanical feedback mechanisms of 56 subjects undergoing decompressive surgery were collected. Preoperative CSM patients showed significant alterations in spatiotemporal gait parameters and postural stability compared with controls. Likewise, angular momentum analysis demonstrates that these patients have globally increased body excursion to maintain dynamic balance. Abstract : Study Design: Prospective cohort study. Objective: The aim of this study was to 1) determine postural stability and spatiotemporal gait parameters and 2) characterize dynamic stability and variances in angular momentum (AM) of preoperative cervical spondylotic myelopathy (CSM) patients compared with healthy controls. Summary of Background Data: CSM is the most common cause of spinal cord dysfunction in the world and can lead to significant functional deficits including proprioception and gait disturbances. Biomechanical feedback mechanisms compensating for these deficits, specifically AM regulation, have remained largely unexplored. Methods: Fifty-six subjects: 32 preoperative Nurick grade 2 or 3 CSM patients and 24 controls were included. Standing balance trials were performed on a single force plate, while walking trials were conducted at self-selected pace over a 15 m runway and a series of five force plates. All trials were recorded with three-dimensional motion analysis cameras and gait modeling software was utilized to calculate stability, spatiotemporal gait parameters, and joint kinematics. Results: Tilted ellipse area, a measure of center of pressure variance and postural stability, was significantly greater among CSM patients (847.54 ± 764.33 mm 2 vs. 258.18 ± 103.35 mm 2, P  < 0.001). These patients had two times as much variance medial-lateral (72.12 ± 51.83 mm vs. 29.15 ± 14.95 mm, P  = 0.001) and over three times as much anterior-posterior (42.25 ± 55.01 mm vs. 9.17 ± 4.83 mm, P  = 0.001) compared with controls. Spatiotemporal parameters indicated that the CSM patients tending to have slower, shorter, and wider gait compared with controls, while spending greater amount of time in double support. Compensatory AM among CSM patients was significantly increased in all three anatomic planes, where whole-body AM was approximately double that of controls (0.057 ± 0.034 vs . 0.023 ± 0.006), P  < 0.001). Conclusion: Preoperative CSM patients showed significant alterations in spatiotemporal gait parameters and postural stability compared with controls, consistent with prior literature. Likewise, angular momentum analysis demonstrates that these patients have globally increased body excursion to maintain dynamic balance. Level of Evidence: 3